FEATURES OF ACCOUNTING POLICY FORMATION OF FOREIGN ECONOMIC ENTERPRISES (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article examines the formation of accounting policy at enterprises engaged in foreign economic activity. The relevance of the study is determined by the growing role of international trade, the complexity of currency regulation, customs procedures, export-import documentation and tax administration. It is substantiated that the accounting policy of enterprises operating in foreign markets cannot be limited to general rules of accounting organization, because it must additionally regulate foreign currency transactions, exchange rate differences, customs value, import duties, export VAT, Incoterms conditions, documentary support of international contracts and internal control over settlements with non-residents. The paper systematizes the elements of accounting policy for exporters, importers, logistics operators and enterprises with combined foreign economic operations. A comparative sample of ten Ukrainian enterprises from agribusiness, food production, retail, e-commerce, logistics and metallurgy is proposed. The choice of enterprises is justified by their involvement in export, import, international transportation, foreign currency settlements and supply chains. For logistics operators, international transport documents, service accounting, route control and synchronization of accounting data with logistics systems are of the greatest importance. The study proposes a risk-oriented model of accounting policy formation that integrates methodological, organizational, tax, customs, digital and control components. Particular attention is paid to ERP systems, electronic document flow, currency risk monitoring and the need to harmonize accounting policy with national standards, IFRS and current foreign exchange regulation. This allows us to consider accounting policies not only as internal accounting regulations, but as a tool for managing risks of foreign economic activity. The practical significance of the article lies in the possibility of using the proposed approach for improving accounting organization and internal control of foreign economic operations.
Keywords: accounting policy; foreign economic activity; foreign currency transactions; accounting; exchange differences; international settlements; digital accounting